Experimental surgery - its role in the medical-surgical education - Villarán, Carlos (1955)
The Amphitheatre of Anatomy in the Faculty of Aged people Hipólito Unanue founded Lima, started 51 years ago, works of Operative Technique in live animals and also of Experimental Surgery. Make the story of what this field of science has been doing among us, to analyze the benefits for Medical Education reported this method of study and to be achieved when the facilities are completed are doing is the subject of this article dedicated to the wise Master as a modest contribution to the just tribute the whole country will be taxed on the occasion of the bicentenary of his birth.